2022
DOI: 10.1177/21514593221117309
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates in Femoral Neck Fractures Treated With Arthroplasty in South Africa

Abstract: Objectives To investigate the mortality rate for neck of femur fractures treated with arthroplasty at a tertiary level unit in South Africa and to evaluate the effect of known risk factors for mortality in neck of femur fractures treated with arthroplasty in the South African context. Design Retrospective cohort study. The main outcome was to determine mortality rates during in hospital stay, at 3 months, 6 months 1 year post surgery. The secondary outcome was to determine factors influencing mortality at 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Recent studies from South Africa (SA) reported 3.3% in-hospital mortality rate, 5.6% at 30 days and 26.7% at 1 year [ 7 ]. The incidence rate for FFH in SA is 68.6 patients per 100,000 population, occurring at a younger average age (60 years) than the international averages.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from South Africa (SA) reported 3.3% in-hospital mortality rate, 5.6% at 30 days and 26.7% at 1 year [ 7 ]. The incidence rate for FFH in SA is 68.6 patients per 100,000 population, occurring at a younger average age (60 years) than the international averages.…”
Section: Introductionmentioning
confidence: 99%